Extraction and characterization of pectic polysaccharides from Choerospondias axillaris peels: Comparison of hot water and ultrasound-assisted extraction methods. (1st February 2023) - Wang, Chao; Li, Jing; Cao, Yi; Huang, Jialu; Lin, Hongyi; Zhao, Tiantian; Liu, Lu; Shen, Peiyi; Julian McClements, David; Chen, Jun; Liu, Chengmei; Liu, Jiyan; et al.
Graphical abstract: Highlights: Polysaccharides were obtained by hot water (HP) and ultrasonic-assisted extraction (UP) Polysaccharide molecular and functional properties depended on extraction method. UP had higher viscosity and better emulsifying properties than those of HP. The α-glucosidase inhibition activity of HP was markedly higher than that of UP. Abstract: Influences of conventional thermal and innovative non-thermal extraction methods on the physicochemical characteristics and properties of pectic polysaccharides from Choerospondias axillaris peels were investigated. Results showed that ultrasound-assisted extracted polysaccharides (UP) had a heterogeneous nature with lower molecular weight (127.7 kDa) and lower neutral sugar content (35.1%) but higher contents of protein (4.8%) and phenolic compounds (5.1%) than those of polysaccharides extracted by hot water (HP). Additionally, the monosaccharide composition results showed that glucose (77.8%) was the most abundant monosaccharide in HP, while arabinose (67.1%) was the most abundant monosaccharide in UP. The ultrasound significantly induced the degradation of polysaccharide chains but reduced the thermal degradation of phenolics. Finally, we found that UP had higher apparent viscosity, interfacial, emulsifying and antioxidant activity but lower α-glucosidase inhibition activity than those of HP. The results indicated that we could obtain polysaccharides with different functional and biological properties by using different extraction methods.